RESILIENCE OF YOUTH SURVIVORS OF THE 2006 YOGYAKARTA EARTHQUAKE - Endah Tri Wulandari; Dwi Ernawati (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2026)
In the face of trauma caused by earthquakes, adolescents strive to adapt and recover from the disaster, a process known as resilience. Resilience is defined as the ability to adapt to tragedies or events that may trigger trauma. Adolescence is a crucial period in life, marking the transition from childhood to adulthood, marked by hormonal changes, independence, risk-taking, emotional reactivity, and significant environmental changes. Puberty is a sensitive period for traumatic events, and this is linked to the development of psychological well-being in adulthood.Adolescent resilience is the result of a series of cognitive and behavioral strategies conceptualized as coping strategies for coping with trauma. However, not all adolescents are able to use these skills to cope. Some resilience efforts are unsuccessful, resulting in negative outcomes. In fact, it has been reported that 24.4% of adolescents who survived an earthquake experienced post-traumatic stress disorder (PTSD). The phenomenon of post-disaster resilience is not fully understood, and there has been limited research. Based on this background, this study aims to analyze adolescent resilience following the 2006 Yogyakarta earthquake. This research is a qualitative phenomenological study. The phenomenological approach in qualitative research focuses on the essence of experience.Based on the data analysis, four themes emerged: the impact of the earthquake, constructive coping mechanisms, resilient personality, and earthquake preparedness. The 2006 earthquake had a significant psychological impact on adolescents. However, adolescents were able to adapt to these difficult conditions and needed external support to develop positive coping mechanisms.